Determinants of Executive Support System: Information Technology, Digital Leadership, and Information Systems - Endah Sabarini, Nur; Ali, Hapzi (Siber International Journal of Digital Business (SIJDB), 2024)
The Determinants of Executive Support System: Information Technology, Digital Leadership, and Information Systems is a scholarly paper within the domain of ESBB, which stands for the European Society for Biopreservation and Biobanking. The objective of this article is to formulate hypotheses that establish causal relationships among variables, which will be utilized in subsequent research. Conducting research across various subjects involves utilizing online libraries, Google Scholar, Mendeley, and other academic online platforms. The research methodology involves utilizing resources available in research libraries, such as e-books and open-access electronic journals. Qualitative descriptive analysis is employed. The outcomes of this article are as follows: 1) Information Technology Determinants of Executive Support System; 2) Digital Leadership Determinants of Executive Support System; and 3) Information Systems Determinants of Executive Support System.